Clinical and immune profiling for cancer of unknown primary site. Issue 1 (13th September 2019) - Haratani, Koji; Hayashi, Hidetoshi; Takahama, Takayuki; Nakamura, Yasushi; Tomida, Shuta; Yoshida, Takeshi; Chiba, Yasutaka; Sawada, Takahiro; Sakai, Kazuko; Fujita, Yoshihiko; Togashi, Yosuke; Tanizaki, Junko; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) confer a survival benefit in many cancer types. Given that the survival outcome for cancer of unknown primary site (CUP) remains poor, we investigated the potential of CUP for immunotherapy. Methods: A total of 164 patients with CUP (favorable subset, 34 patients; unfavorable subset, 130 patients) who were treated between January 2009 and March 2017 was identified from a review of medical records at Kindai University Hospital. They included 92 patients for whom pretreatment tumor tissue was available both for determination of programmed cell death–ligand 1 expression and tumor-infiltrating lymphocyte (TIL) density by immunohistochemistry (IHC) and for immune-related gene expression profiling (irGEP). The results of irGEP for CUP were compared with published data for ICI-treated solid cancers classified into progressive disease (PD) and non-PD subsets according to their best response to ICIs. Results: The median overall survival of all CUP patients was 29.3 months (95% confidence interval [CI], 15.7–not reached) and 7.1 months (95% CI, 5.0–9.4) for favorable and unfavorable subsets, respectively. IHC and irGEP revealed that pretreatment immune activity—including expression of immune checkpoint molecules—for CUP was similar to that for ICI-responsive malignancies (antitumor immune cell signatures: CUP versus PD, P  = 0.002–0.067; CUP versus non-PD, P  = 0.591–0.999), although VEGFA expression was associated with suppression of antitumor immunity in CUP ( P  = 0.008, false discovery rate = 0.010). In addition, one case of CUP in the unfavorable subset that was associated with prominent PD-L1 expression on TILs and showed a durable response to nivolumab is presented. Conclusions: The survival outcome of CUP remains unsatisfactory. However, our clinical and immune profiling of CUP has revealed a potential to benefit from immunotherapy, with ICIs thus being a potential option for CUP treatment.